ESTUDO IN VITRO DAS ALTERAÇÕES EM SUBSTRATO DENTÁRIO BOVINO SUBMETIDO À EROSÃO ÁCIDA E ESCOVAÇÃO SIMULADA - Lawder, Juliana Aparecida de Campos (2010)
Aiming to check the pH values and ability to seven drinks previously selected, the action beverage on the structure of bovine enamel and dentin and the effect of brushing with dentifrices one of which is indicated for lesions of acid erosion a study was conducted in vitro. We obtained 36 fragments of bovine teeth, with 18 enamel and dentin of 18, which remained immersed in grape juice for 10 minutes and then immersed in artificial saliva for 60 minutes. This cycle was repeated 4 times every 6 hours. After acid challenge, bodies were prepared with proof-of-four fragments each (2 of 2 enamel and dentin). Six specimens used in ev ence were submitted to 16,000 brushing cycles using soft bristle brushes and toothpaste solution / distilled water or distilled water only. The brushing was performed with two dentifrices, diluted in ratio 1:2, and only distilled water (control). The change in surface roughness and hardness were determined by the difference between roughness obtained after erosion (erosive) and after brushing (toothpaste, water). Moreover, we observed in SEM images of enamel and dentin subjected to erosion and brushing. The results were subjected to statistical tests (ANOVA, Bonferroni test (p ≤ 0.05) and t-student test) which showed: soaking in grape juice caused higher roughness on the surfaces when compared to immersion in artificial saliva (p = 0.0058) with higher amount of crystals when the surfaces were brushed with the toothpaste when compared to brushing with distilled water and a correlation between surface roughness, soaking in acid beverage and brushing. Through the results obtained, it can be concluded that there was loss of tooth structure when it was subjected to immersion in acid beverage. The variations in structure loss was dependent on whether there is brushing with toothpaste after exposure and both dentifrices tested were able to accelerate the wear of tooth surfaces subject to erosion.